JOHN CALVIN ON SOCIAL CHALLENGES - PC Potgieter (Acta Theologica)
John Calvin’s interpretation of Holy Scripture as the infallible Word of God dominated his approach to socio-economic, sociopolitical and human relation issues. This article endeavours to indicate that his 16th-century views have not lost their relevance for the current paradigm on social challenges. To him, theology was no mere theoretical or academic field; it always tended to become a way of living within the sphere of God’s providence. He thus emphasised the stewardship of man in God’s creation. Whatever affliction people experienced, be it caused by natural disasters or by human disrespect for society, Calvin felt it as profound grief, so that he urged the community to get involved where aid was required. His written legacy abounds in guidelines for dealing with various kinds of social and economic issues. His clear view and perspectives on the social challenges of his era provide more than enough to consider in the 21st century.